Partisipasi Politik Masyarakat Dalam Pemilihan Gubernur Dan Wakil Gubernur Riau Putaran Ke Dua Di Kota Pekanbaru Tahun 2013 (Studi Kasus di Kelurahan Air Hitam Kecamatan Payung Sekaki) - SAMSUL BAHRI; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Political participation of the community in direct local elections is an important institution in any democratic country like Indonesia . Local elections is also a means of political education for the people who are directly and openly . That is expected to increase public awareness about democracy . Local elections emphasize democratization process better and deeper . Local elections laden with political competition among the participants . Researchers study detailing the problem as follows : How can public participation during the day ( voting ) , and whether the factors that cause a lot of abstentions or no vote on the election of the Governor and Deputy Governor of Riau second round of 2013 in the Village of Air Hitam District of Payung Sekaki, Pekanbaru .This research was conducted with descriptive qualitative method with purposive sampling technique and key person in order to build knowledge representations based on a relatively deep and detailed . While the analysis of data using triangulation of data and data analysis with interactive models of data .After doing research and data processing can be concluded that the public's understanding of the elections and the relatively low level of political participation , as well as the factors that determine cause many non-voters or did not vote on the election of the Governor and Deputy Governor of Riau second round of 2013 in the Village of Air Hitam District of Payung Sekaki Pekanbaru city largely because of socioeconomic factors , psychological factors and factors of rational choice and the apathy and indifference of the society towards the common election because of the crisis of public trust in the leader . Keywords : Participation , politics , society .